Investigation of the dependence of the activity concentration of natural and artificial radionuclides on particle size in surface soil - Mitsios, I. K.; Karangelos, D. J.; Anagnostakis, M. J. (HNPS Advances in Nuclear Physics, 2019)
Surface soil radioactivity is being studied at NED-NTUA since almost thirty years. The last few years this research has expanded to the study of soil particle size fractionation of radionuclides. The purpose of the present work was to study the tendency of many radionuclides to accumulate in the smaller particle size fractions. To this end, soil samples were collected from an area in the NTUA Campus where 241Am contamination, due to a failed 241Am-tipped lightning rod, had been previously detected. The samples were separated into size fractions using a sieving machine and analyzed by gamma spectrometry to determine 210Pb, 241Am, 234Th, 228Ra, 228Th, 226Ra, 7Be, 137Cs and 40K. The activity concentrations of these nuclides were found to significantly differ among the size fractions examined.